2021
DOI: 10.1101/2021.03.31.21254115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic epidemiology of SARS-CoV-2 in Russia reveals recurring cross-border transmission throughout 2020

Abstract: SARS-CoV-2 has spread rapidly across the globe, with most nations failing to prevent or substantially delay its introduction. While many countries have imposed some limitations on trans-border passenger traffic, the effect of these measures on the spread of COVID-19 strains remains unclear. Here, we report an analysis of whole-genome sequencing of 3206 SARS-CoV-2 samples from 78 regions of Russia covering the period between March and November 2020. We describe recurring imports of multiple COVID-19 strains thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Similar studies have been reported from a plethora of countries around the world including the UK, Ireland, Russia, India, Qatar etc. [26,[33][34][35][36]. These studies provide valuable information on the routes of importation of new strains and the emergence of critical mutations that change key parameters such as transmissibility or virulence, as was recently highlighted by the discovery of the B.1.617 variant and its B.1.617.2 sub-lineage in India [37], which led to a surge of SARS-CoV-2 infections in Delhi.…”
Section: Resultsmentioning
confidence: 98%
“…Similar studies have been reported from a plethora of countries around the world including the UK, Ireland, Russia, India, Qatar etc. [26,[33][34][35][36]. These studies provide valuable information on the routes of importation of new strains and the emergence of critical mutations that change key parameters such as transmissibility or virulence, as was recently highlighted by the discovery of the B.1.617 variant and its B.1.617.2 sub-lineage in India [37], which led to a surge of SARS-CoV-2 infections in Delhi.…”
Section: Resultsmentioning
confidence: 98%
“…Since the beginning of the pandemic, the distribution of genetic lineages in the Russian Federation has notably changed [ 20 , 21 , 22 ]. In March 2020, the diversity was limited to a few genetic lineages, of which B.1 and B.1.1 were dominant (35.5% and 46.3% respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Our procedure for detection of imports is conservative in that it does not allow repeated imports along the same phylogenetic lineage. It generally yields fewer imports than an alternative approach using Treetime [ 35 ], but the imports detected using maximum parsimony are nearly always also supported by Treetime [ 36 ]. The imports inferred under this definition matched well the clusters of Russian sequences observed in phylogenies.…”
Section: Resultsmentioning
confidence: 99%